Phantasma / (3ghGji (B- (3gOjg CMeOjs - Hedieh Ahmadi (Tehran; Self-published, 2018)
Phantasma reviews memories from a lost place: Qeshm Island, located in the Persian Gulf, has been going through a constant transformation in recent years. Tourism has changed the face of the island and traces of human intervention can be increasingly seen even in the most remote areas of Qeshm. The photos in the book chronicle my several visits to the island, describing an almost dream-like memory that can never be returned to. The book$1 (Bs binding has been designed in a way that the viewer sees every photo almost twice. The framed-within-a-frame style of the design creates a narrative that one can easily set foot into or move out of, and the repetitions aim to induce memories into the reader$1 (Bs mind. Edition 43/100s
English; Persian
Keywords: N4390-5098 Visual Arts. Exhibitions; Iran